Epidemiology of traumatic and overuse injuries in Swiss professional male ice hockey players - Brunner, R.; Bizzini, M.; Niedermann, K.; Maffiuletti, N. A. (Orthopaedic Journal of Sports Medicine, 2020)
Background: Ice hockey injury patterns in Europe were last evaluated in the 1990s.